FREQUENCY AND DISTRIBUTION OF BLOOD GROUPS IN THE DONORS OF A RURAL HOSPITALS, BARASAT, 24 PARGANAS, WEST BENGAL, INDIA - DR. ASHIS KUMAR SAHA; DR.BIBHAS SAHADALAL (International Journal of Pharma and Bio Sciences, 2016)
Nearly 400 red blood cell antigens have been grouped into 30 major blood groups, of which, ABO and Rhesus blood group systems are most important for prevention of serious life threatening transfusion reaction, parental testing, legal medicine and extensive population based genetic studies. Our aim of this study was to determine as well as comparing the frequency of ABO and Rhesus blood group systems in the blood donors of Cancer Hospital, Barasat, West Bengal. A retrospective study was conducted in a blood bank of this cancer hospital over a period of three years. The blood was tested and grouped by test tube agglutination technique by commercially available standard monoclonal antisera. Out of total 5128 blood donors, male and females were 4227 (82.42%) and 901 (17.57%) respectively. Regarding ABO blood group systems, B was found to be the commonest (1873, 36.52%), followed by O (1604, 31.27%), A (1130, 22.03%) and AB (521, 10.15%). Regarding Rhesus blood grouping systems, 4987 (97.25%) was Rh positive and 141 (2.74%) Rh negative. This study may be a corner-stone of Improvement of the blood bank data base system as well as blood transfusion services required in case of emergencies. It can prevent miss-matched severe life threatening blood transfusion reaction. It can be future predictor of several morbid and mortal diseases.